ON COMMUTING TRACES OF GENERALIZED BIDERIVATIONS OF PRIME RINGS - Ali, Asma; Shujat, Faiza; Khan, Shahoor (Italian Journal of Pure and Applied Mathematics, 2015)
In this paper, we prove some theorems on symmetric generalized biderivations of a ring, which extend a result of Vukman [9, Theorem 1] and a result of Bresar [3, Theorem 4.1].